Improving Employee Performance at Banjarwangi Community Health Center: The Role of Leadership, Work Culture, and Work Environment in Enhancing Work Motivation - Jupri Pringadi; Asti Nur Aryanti; Nunung Ayu Sofiati; Gurawan Dayona Ismail; Palupi Permata Rahmi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Employee overall performance is a vital determinant of carrier pleasant in public health centers. The emergence of various provider-associated troubles suggests that declining overall performance is closely linked to organizational situations. This observe investigates how management, organizational subculture, and the paintings surroundings affect paintings motivation and, in flip, shape employee overall performance on the Banjarwangi Public health facility. work motivation is located as a mediating variable. using a quantitative survey design, facts have been accrued thru questionnaires and analyzed with the Partial Least Squares–Structural Equation Modeling (PLS-SEM) technique. The loading component assessment suggests that every construct is represented by using its most dominant indicator: the Informational function (X12) strongly reflects management (0.964); Involvement (X2.1) satisfactory represents Organizational subculture (zero.896); the Non-physical paintings surroundings (X3.2) is the most powerful indicator for the paintings surroundings assemble (zero.918); the need for strength (Y2) leads the paintings Motivation construct (zero.913); and Contextual performance (Z2) is the most prominent indicator of employee overall performance (0.926). these results spotlight how informational leadership, employee involvement, supportive non-bodily conditions, the preference for have an effect on, and contextual behaviors shape each variable. The SEM-PLS consequences exhibit that the model has sturdy explanatory functionality, with R² values of zero.562 for paintings Motivation and 0.678 for worker performance. most of the predictors, Organizational way of life exerts the maximum significant impact on paintings Motivation (0.392), observed through the paintings environment (0.322), at the same time as management contributes most effective marginally (zero.071). This indicates that motivation and performance are extra strongly pushed via cultural and environmental factors than by way of management practices. in addition analysis indicates that management, organizational tradition, and the paintings surroundings every have a fantastic and vast influence on paintings motivation. paintings motivation and organizational tradition also substantially decorate worker overall performance, whereas leadership and the paintings environment do not at once impact performance in a sizable way. Mediation trying out exhibits that paintings motivation fully mediates the results of management and the paintings environment on performance, and partly mediates the impact of organizational subculture. usual, the findings underscore the crucial position of labor motivation in improving worker performance. Efforts to raise overall performance ought to prioritize techniques that fortify motivation specially thru supportive management behaviors, the cultivation of a carrier-driven organizational culture, and the status quo of a greater conducive work surroundings.